2005
DOI: 10.1007/s00424-005-1480-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and insights on function of potassium channel TWIK-1 in mouse kidney

Abstract: Renal distribution and function of TWIK-1, a member of the two-pore-domain potassium channel family, was studied in mouse kidney. TWIK-1 is expressed in apical and subapical localizations of proximal tubule and cytoplasmic sites of thin and thick ascending limbs, distal convoluted tubules and medullary collecting duct. Studies in mice lacking intact TWIK-1 (twik-1 -/-) and wild-type mice (twik-1 +/+) revealed an attenuated ability to increase renal phosphate (Pi) reabsorption and stabilize plasma Pi concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…First, the TASK-1 channel is only 14 pS (2). Second, TWIK-1, a 34-pS, weakly inward rectifying and ATPinsensitive K ϩ channel, appears only intracellularly located in mouse CCD cells (24), with no detectable activity in cell membranes (20). In addition, TWIK-1 is insensitive to pH i in cell-excised inside-out membrane patches of Xenopus oocytes (14).…”
Section: Molecular Candidates For Basolateral K ϩ Channels In Mouse Cmentioning
confidence: 99%
“…First, the TASK-1 channel is only 14 pS (2). Second, TWIK-1, a 34-pS, weakly inward rectifying and ATPinsensitive K ϩ channel, appears only intracellularly located in mouse CCD cells (24), with no detectable activity in cell membranes (20). In addition, TWIK-1 is insensitive to pH i in cell-excised inside-out membrane patches of Xenopus oocytes (14).…”
Section: Molecular Candidates For Basolateral K ϩ Channels In Mouse Cmentioning
confidence: 99%
“…12,13 Immunohistochemistry identified Npt2a to be localized predominantly in the apical plasma membrane of S1-S3 segments of the proximal tubule. 6,14,15 Npt2c has a similar cellular distribution with greater abundance in S1 segments. 5,16,17 Genetic defects in G sa result in impaired PTH-induced retrieval of Npt2a, resulting in a failure to respond with increased urinary P i excretion: a disease commonly referred to as pseudohypoparathyroidism type Ia or Ib (depending on the presence or absence of skeletal defects, respectively).…”
mentioning
confidence: 96%
“…However, in endogenous systems, expression of TWIK-1 has been documented in various tissues, including the brain, heart and kidney 3 . Mice deficient in TWIK-1 show defects in phosphate transport in the proximal tubule and water transport in the medullary collecting duct of kidney, as well as deviations in the resting membrane potential of pancreatic b cells 4,5 . In addition, it has been recently reported that TWIK-1 conducts inward leak Na þ currents during pathological hypokalaemia in cardiomyocytes 6 .…”
mentioning
confidence: 99%